Evaluation of the user experience for a point of care molecular test for causes of vaginitis - Barbara Van Der Pol; Rebecca Lillis; Irving Nachamkin; Stephen Young; LaShonda Crane; Jacqueline Brown; R. Lamar Parker; Alice Weissfeld; Xiaohong Liu; Christina Huang; Aarthi Raman (BMC Infectious Diseases)
Abstract Background Vaginitis is a major cause of healthcare visits in the US, costing over $1.2 billion annually. Point-of-care (POC) nucleic acid amplification tests (NAATs) could improve accuracy of diagnosis and treatment during initial visit for vaginitis compared to send-out NAATs. Methods A secondary analysis of data was collected from test operators at POC testing sites where the Xpert Xpress Multiplex Vaginal Panel test (“MVP test”) was performed. Users completed a survey assessing their experience with the instrument system and the PCR-based MVP test. Results The MVP test demonstrated consistent performance, measured by positive and negative percent agreement, across all user categories, including both trained and untrained staff. Performance was evaluated based on job function (clinicians, non-clinicians, support staff) and educational level (bachelor’s degree or higher, associate’s degree or some college, high school diploma/general educational development (GED) with technical certification), with no significant differences in performance (P >0.082 and P >0.050, respectively). User feedback from 19 operators showed that 15/19 (79%) of users found the GeneXpert Xpress Instrument System easy to set up, and 18/19 (96%) found the test instructions easy to follow. Users described the system as user-friendly with clear instructions and helpful videos. Overall, 19/19 (100%) agreed that the MVP test was easy to perform. Conclusions Availability of accurate POC diagnostics will only be useful if the test can be performed by any potential user. Our study results suggest that the MVP test was acceptable to users and that results were accurate regardless of user qualifications. Thus, this test has the potential to improve the immediate clinical outcome by supporting accurate, same day treatment for causes of vaginitis.